A new species related to Anorthoa changi from Wuyishan National Park (Lepidoptera, Noctuidae, Hadeninae) - Rui Xie; Liang Guo; Chenbin Wang; Hongdi Gao (Biodiversity Data Journal)
Anorthoa Berio, 1980 is a genus within the subfamily Hadeninae . This genus has a close relationship with the rama species complex of the genus Harutaeographa. It comprises three species groups: the munda-group, the angustipennis-group and the rubrocinerea-group. The species Anorthoa changi Ronkay & Ronkay, 2001 from Taiwan Island belongs to the rubrocinerea-group.A new species related to Anorthoa changi Ronkay & Ronkay, 2001, is described from Wuyishan National Park, China. The new species can be distinguished from its sister species by its larger size and some differences in the genitalia. Now, the number of species in the genus Anorthoa is increased to eleven.